Reliability in power electronics and electrical machines : industrial applications and performance models - Kaboli, Shahriyar, 1975-; Oraee, Hashem, 1957- (Advances in computer and electrical engineering (ACEE) book series., 2016)
"This book provides an in-depth analysis of reliability in electrical energy converters as well as strategies for designing dependable power electronic converters and electrical machines by featuring a comprehensive discussion on the topics of reliability design and measurement, failure mechanisms, and specific issues pertaining to quality, efficiency, and durability"--